The complete chloroplast genome sequence of Thymus quinquecostatus var. japonicus (Lamiaceae), an endemic to Ullenung Island of Korea - Hyoung Tae Kim; Jae-Hong Pak; Jung Sung Kim (Mitochondrial DNA. Part B. Resources, 2020)
The complete chloroplast (cp) genome sequence of Thymus quinquecostatus var. japonicus, an endemic species to Ulleung Island of Korea and used as plant material for folk remedies, was firstly analyzed in this study. It showed a typical circular structure composed of 151,782 bp in length and comprised of a large single-copy region (82,903bp) and a small single-copy region (17,667 bp) which were separated by two inverted repeat regions (25,606 bp). From the phylogenetic analyses of related taxa using the complete chloroplast genome sequences, it was proved that T. quinquecostatus var. japonicus is sister to the member of genus Mentha within the subfamily Nepetoideae.